Neonatal Bacterial Infection - Resch, Bernhard (IntechOpen, 2013)
Neonatal sepsis still remains a significant cause of morbidity and mortality in the newborn, particularly in preterm, low birth weight infants. Despite advances in neonatal care, overall case-fatality rates from sepsis may be as high as 50%. Clinical signs of bacterial infection are vague and non-specific, and up to now there exists no easily available, reliable marker of infection despite a large bulk of studies focussing on inflammatory indices in neonatology. Every neonatologist is faced with the uncertainty of under- or over- diagnosing bacterial infection. In this book three topics will be discussed: clinical presentation including a general approach to sepsis neonatorum and two distinct diagnoses pneumonia and osteomyelitis diagnostic approaches including C-reactive protein and the immature myeloid information, and prevention and treatment of bacterial infection with immunoglobulins.